Legal Review of Business Competition in Preventing Predatory Pricing Practices Using Buy One Get One Free and Discount Voucher Methods in the Modern Retail Market - Grace Henni Tampongangoy (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
This study aims to provide an overview of the role of law enforcement and government in business competition to prevent predatory pricing practices using the Buy One Get One Free (BOGO) method and cheap redemption under Law Number 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition in modern retail markets. This research employs empirical legal methods focusing on the modern retail market, specifically on minimarket operators such as Alfamart, Indomart, and Alfamidi. The findings indicate that the competition authority (government) plays a significant role in preventing predatory pricing practices through: 1) market supervision, including monitoring market and business activities to detect signs of predatory pricing; 2) conducting thorough investigations into allegations of predatory pricing; 3) enforcing laws with decisive actions against businesses found guilty of predatory pricing; and 4) raising public and business awareness about the risks associated with predatory pricing practices. The research concludes that predatory pricing practices using the BOGO method can distort business competition and harm consumers, highlighting the crucial role of competition law in prevention.